Effectiveness of 8-Week Learning Recovery Curriculum in Improving the Reading Performance of Pupils - Dionglay, Edna Dollison; Bembo MAEd, Aba Marie Laurence Escarcha; Janer, Susan Salvador (FKIP Universitas Lampung, 2023)
Effectiveness of 8-Week Learning Recovery Curriculum in Improving the Reading Performance of Pupils. This study determined the effectiveness of an 8-week curriculum in improving the reading performance in English of Grade Three Pupils. This employed descriptive and pre-experimental research design. The respondents were the twenty-five (25) Grade Three pupils of a public elementary school in Sorsogon City Division, Philippines. The pre-test and post-test results of the Comprehensive Rapid Literacy Assessment (CRLA) were utilized. The study found that most of the Grade Three pupils are Moderate Refreshers. After the post-test 40% of the pupils improved their skills in reading. Intervention through the implementation of the 8-week Learning Recovery Program was effective in improving the reading performance of pupils in English. It was recommended that the 8-Week LRC as an intervention must be implemented, and enhanced. Keywords: 8-week learning recovery program ; reading performance; pre-test and post-test DOI: http://dx.doi.org/10.23960/jpp.v13.i3.202306